PENGENDALI WAKTU PENYIRAMAN PADA TANAMANHIDROPONIK MENGGUNAKAN IC 555 - Watiningsih, Tri; -, Kholistianingsih; Wahjudi, Dodi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
ABSTRACT Availability of cropland is the reason why they do not want to plant crops, especially vegetables such as eggplant, cabbage, chilli, as academics eager to implement and introduce hydroponic plants so that the need for hygienic vegetables that can be realized. Along with the question, it is necessary to increase public participation for the introduction in fulfilling the need for vegetables dilahan own more hygienic through Research Lecturer Beginners